Characterisation of frother properties in coal preparation process water. (15th August 2017) - Bournival, Ghislain; Muin, Syeda R.; Lambert, Noel; Ata, Seher
Graphical abstract: Highlights: Behaviour of bubbles in coal plant recycled water tested with frother. Frother addition less effective in high ionic strength samples for coalescence time. Frother more effective in high ionic strength samples in lowering bubble size. Coal preparation plants should monitor water quality. Abstract: From an environmental and economic perspective coal handling and preparation plants are under increasing pressure to reduce their consumption of fresh water and to strictly follow tight standards and specifications to release process water. Many coal washeries use recycled water as part of their water management strategy, which contains a higher content of inorganic electrolytes. In this study, five water samples from four coal washeries were analysed. The effect of methyl isobutyl carbinol (MIBC) frother was tested to evaluate the influence of water composition on the persistence of bubble pairs and the effectiveness of MIBC in preventing coalescence in a quiescent and dynamic environment, respectively. It was shown that the coalescence time was longer for bubbles in water samples of higher ionic strengths. However the effectiveness of an addition of MIBC was weakened in these solutions. It was also established that the water samples with higher ion content produced smaller bubbles in a laboratory flotation cell. In contrast to the binary coalescence experiment, the addition of MIBC appeared to be more effective in reducing the bubble size whilst a higher electrolyte concentration is present. The sensitivity of the effects of inorganic electrolytes on the bubble-bubble interactions suggests that coal washeries may benefit in monitoring the quality of the water employed in the flotation circuit.